2019
DOI: 10.1182/bloodadvances.2019000399
|View full text |Cite
|
Sign up to set email alerts
|

Fetal hemoglobin does not inhibit Plasmodium falciparum growth

Abstract: Key Points P falciparum growth is not inhibited in either cord or heterozygote hereditary persistence of fetal hemoglobin erythrocytes. P falciparum growth in fetal hemoglobin erythrocytes is oxygen independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Furthermore, earlier reports suggested that Plasmodium parasites do not develop normally in red blood cells containing fetal hemoglobin ( Wilson et al., 1977 ). These data have been challenged by more recent study results that show that P. falciparum and P. vivax parasites invade cord blood-derived RBCs as well as RBCs from peripheral blood ( Archer et al., 2019 ; Roobsoong et al., 2015 ). Concordantly, the invasion capacity of the parasites in our model was not reduced in reticulocytes originating from cord blood.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, earlier reports suggested that Plasmodium parasites do not develop normally in red blood cells containing fetal hemoglobin ( Wilson et al., 1977 ). These data have been challenged by more recent study results that show that P. falciparum and P. vivax parasites invade cord blood-derived RBCs as well as RBCs from peripheral blood ( Archer et al., 2019 ; Roobsoong et al., 2015 ). Concordantly, the invasion capacity of the parasites in our model was not reduced in reticulocytes originating from cord blood.…”
Section: Discussionmentioning
confidence: 98%
“…The delay in the onset of parasitemia in our experiments cannot be attributed to maternal antibodies because the dams were naïve to P. yoelii . Although early studies suggested the prevalence of HbF during neonatal period as another possible reason in the protection of infants from P. falciparum infection 16 , subsequent studies demonstrated that cord RBCs can be infected with P. falciparum 18 , 19 . Moreover, HbF cannot account for the suppressed parasitemia in NB mice because, unlike humans, mice RBCs do not have HbF 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies suggested that P. falciparum growth is arrested in cord blood erythrocytes due to HbF 16 , 17 . Subsequent reports demonstrated that Hbf does not inhibit P. falciparum growth in infant red blood cells 18 , 19 . The dietary elements of neonatal period can also be contributing to the protection of infants from malaria 20 .…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that sickle red cells can modify the parasite gene expression at transcriptional level through red cell microRNA that translocate into the parasite (39). This raises the possibility that other abnormal hemoglobin, such as HbF, may as well contribute to protection by reducing var gene expression and cytoadhesion (40). HbF has been suggested to work together with maternally acquired antibodies to protect infants from malaria (41) perhaps by impairing cytoadhesion and promoting clearance of IE.…”
Section: Discussionmentioning
confidence: 99%